Morphological study of myocardial capillaries in endurance trained rats. Issue 2 (June 1990) - Qu, X
Abstract : In this morphological study of the effects of training on myocardial capillaries, four week old Wistar rats were selected to accept four months of treadmill training. The rats were then sacrificed for morphological study of myocardial capillaries by means of perfused Chinese ink, AKP stain and ultrathin section methods. The results showed that the number of capillaries in trained rats was increased markedly by 14.8 per cent (P less than 0.05) in the outer layer and 13.7 per cent (P less than 0.05) in the inner layer. The ratio of capillaries to myocardial fibres was increased by 17.6 per cent and 13.7 per cent (P less than 0.05) respectively. The area and girth of capillaries in the trained rats were increased by 25 per cent and 26 per cent (P less than 0.01) respectively. Collateral branches in the trained rats were also increased and were more irregular in shape or appeared locally expanding and tortuous. Unopened capillaries were often observed in the control rats, while in the trained rats, no unopened capillaries were observed. In addition, the small vacuoles in the cytoplasm of endothelial cells were also increased.